A configuration study on rural residents’ willingness to participate in improving the rural living environment in less-developed areas—Evidence from six provinces of western China - Su, Yiqing; Qiu, Yabiao; Xuan, Yuan; Shu, Quanfeng; Li, Zhengxiao (Frontiers in Environmental Science, 2023)
Maintaining the sustained improvement of human living environments in rural areas while improving habitats poses a substantial challenge. While promoting participation by rural residents is key to achieving the improvement of rural living environments, existing studies have mostly focused on the "net effect" single factors have on their participation. However, few studies have considered the combined effects of multiple characteristics in complex contexts. In this study, a revised model of planned behavior is constructed, based on configuration theory; the histories of pathways that influence rural households' willingness to participate in improving rural living environments are also explored. The perspective of concurrent causality is adopted, and this study examines whether a 'mutual substitution effect' exists between the antecedent conditions in different paths. A questionnaire survey was conducted in six provinces (including autonomous regions) in less-developed areas of China. Six configuration paths of rural residents' higher willingness to participate in the improvement of rural living environments were obtained using fuzzy-set qualitative comparative analysis. The results show that: (1) in the path of high willingness to participate, the behavioral attitudes characterized by the "trustworthiness of village leaders" and "group identity" play the central role. "Social capital" and the "trustworthiness of village leaders" have a mutual substitution effect. (2) When using positive behavioral attitude evaluation as a core condition, "educational level" and "environmental awareness" have a mutual substitution effect. "Household income level", as the marginal condition, has a mutual substitution effect with "environmentally friendly habits". Therefore, to increase rural residents' willingness to participate in improving rural living environments in less-developed areas, the level of the "trustworthiness of village leaders" and "group identity" should be raised. In addition, depending on the "mutual substitution effect" between different conditions, to achieve the same improvement in rural areas with a low level of "social capital", the focus should be on improving the "trustworthiness of village leaders". For rural areas with a slight difference in "household income level", the focus should be on promoting the formation of "environmentally friendly habits" among rural residents.